"What! Still alive?!" : Jewish survivors in Poland and Israel remember homecoming - Rice, Monika (Syracuse, New York : Syracuse University Press, 2017)
"What! Still Alive?!" offers a powerful and deeply affecting examination of the complex memories of Jewish survivors returning to their homes in Poland after the Holocaust. These survivors left unparalleled testimonies of their first impressions with the Jewish historical commissions from 1944 to 1950. As many survivors found they were no longer welcome by their Polish neighbors, they chose to settle in the new state of Israel. Again, these surviving Jews left testimonies describing their postwar returns. In "What! StillAlive?!," Rice investigates the transformation of survivors' memories from the first account after their initial return to Poland and later accounts, recorded at Yad Vashem in Jerusalem between 1955 and 1970. Through close readings of these firsthand narratives, Rice traces the ways in which the passage of time and a changing geopolitical context influenced the survivors' memories.
In search of postwar memory -- The returning survivors: historical context -- The Central Jewish Historical Commission and its project of documenting survivors' stories -- First encounters with the neighbors as represented in the Jewish Historical Institute collection -- Yad Vashem testimonies in the context of Israeli history -- Memories of the first encounters as represented in the Yad Vashem collection -- Comparative analysis of the data: memory on a curve -- Toward building a collective memory.
Online resource; title from PDF title page (EBSCO, viewed January 9, 2018).
Includes bibliographical references and index.
JSTOR
Keywords: Żydowski Instytut Historyczny im. Emanuela Ringelbluma; Yad ṿa-shem, rashut ha-zikaron la-Shoʼah ṿela-gevurah.; Yad ṿa-shem, rashut ha-zikaron la-Shoʼah ṿela-gevurah; Żydowski Instytut Historyczny im. Emanuela Ringelbluma; Jews -- Poland -- History -- 20th century; Holocaust survivors -- Poland -- Attitudes; Holocaust survivors -- Israel -- Attitudes; World War, 1939-1945 -- Concentration camps -- Liberation; Poland -- Ethnic relations; Juifs -- Pologne -- Histoire -- 20e siècle.; Survivants de l'Holocauste -- Pologne -- Attitudes; Survivants de l'Holocauste -- Israël -- Attitudes; Guerre mondiale, 1939-1945 -- Camps d'internement -- Libération.; HISTORY -- Europe -- Western; Internment camps; Liberty; Holocaust survivors -- Attitudes; Ethnic relations; Jews; Israel; Poland; 1900-1999; History